Seroprevalence and risk factors of Chikungunya in Ethiopia: a systematic review and meta-analysis - Dagnaw, Gashaw Getaneh; Gessese, Abebe Tesfaye; Abey, Solomon Lulie; Bitew, Abebe Belete; Berrie, Kassahun; Dejene, Haileyesus (Frontiers in Public Health, 2025)
IntroductionThe resurgence of the Chikungunya virus has led to public health concerns due to frequent epidemics worldwide. Chikungunya was first detected in Ethiopia in 2016, and it has been identified in various regions. However, the current status of the disease in Ethiopia remains unknown, underscoring the need for updated information.ObjectiveTo provide up-to-date epidemiological data on the status of Chikungunya in Ethiopia.MethodsA systematic review and meta-analysis were conducted using the PubMed, Scopus, and Google Scholar databases in accordance with the PRISMA guidelines, the literature search was conducted from September to October 2024. The search terms used included ‘Chikungunya,’ ‘Chikungunya Virus,’ ‘Prevalence,’ ‘Seroprevalence,’ ‘Risk Factor,’ and ‘Ethiopia.’ The inclusion criteria covered online articles published between 2016 and 2024 in English and published in Ethiopia. The quality assessment involved independent expert evaluations, and publication bias was assessed using Begg’s and Egger’s tests. The analysis was performed using STATA 17 software.ResultsA total of five articles met the eligibility criteria and were included in the data extraction. The pooled seroprevalence of Chikungunya in Ethiopia was 24.0%. The highest seroprevalence was reported in the Southern Nations, Nationalities, and Peoples’ Region (SNNPR), at 43.6%, while the lowest seroprevalence was in Dire Dawa, at approximately 12.0%. Factors such as occupation, education, age, and sex contributed to the variation in seroprevalence of the disease. Subgroup meta-analysis revealed heterogeneity across the types of studies included. No indications of publication bias or small-study effects were found according to Begg’s test or Egger’s test.Conclusion and relevanceThe pooled prevalence of Chikungunya underscores its significance in Ethiopia, necessitating proactive monitoring, active viral disease surveillance, and robust health system enforcement.